Simulation and protection a ventilator for acute respiratory distress syndrome using MATLAB (Journal of Hama University, 2025)
In this research, we present a model for a respirator designed to support patients suffering from Acute Respiratory Distress Syndrome (ARDS). The study aims to calibrate this device and simulate changes in oxygen levels, oxygen saturation, and carbon dioxide during a 120-minute therapeutic session. Additionally, blockchain technology is employed to ensure the protection of vital medical data from tampering and cyberattacks, thereby enhancing the security and privacy of sensitive health information.The research incorporates mathematical equations to calibrate the proposed model and calculate essential vital signs, including equations for oxygen flow, tidal volume, ventilation, and the partial pressure of oxygen in the blood. The simulation demonstrates that the respirator can achieve stabilization and improvement in patients' vital signs, with the model including warning messages when values exceed acceptable and normal ranges.Furthermore, the study confirms that utilizing blockchain significantly enhances the security and privacy of health data, ensuring uninterrupted treatment. The integration of blockchain technology into respirators provides a high level of security and effectiveness, thereby improving healthcare outcomes for patients with ARDS, who require continuous transmission of patient data through vital sensors. It is, therefore, critical to protect the privacy of this data to safeguard patients' lives. The research also suggests further development of this technology and its integration with other healthcare systems to achieve optimal outcomes and to facilitate widespread use of these devices with a high level of security.
Keywords: Blockchain; Acute Respiratory Distress Syndrome; Cybersecurity; Device Calibration; MATLAB; Respirators